Inovação e Sustentabilidade:: LACIS/FAU/CDS/FGA-UnB - Naves Blumenschein, Raquel; Ferrari Tomé, Maria Vitória (Sustainability in Debate, 2011)
The twenty-first century challenges require the acceleration of the technological paradigms changes in order to minimize environmental impacts and waste of natural resources, and reduce emissions and pollution. Among the main impactful activities on the planet quotes the production of the built environment which is a result of the processes of the productive chain of the construction industry (PCCI). The study of the acceleration of technological paradigm shift is linked to the study of the innovation process. The understanding of the influence vectors of the innovation process of PCCI requires studies that identify how new ideas are generated and integrated into the production process and products. These studies require the development of specific models which must be tested in practice through pilot projects. Studies aimed at identifying forces responsible for the emergence of innovations and demonstrating the relations between different actors and vectors of influence become relevant. In this sense, among the contributions that are being given in the University of Brasilia it can be quoted the Lacis/UnB. The aim of this paper is to present the trajectory of Lacis/FAU/CSD/FGA-UNB in the last five years and the main results of applied research with a focus on the productive chain of the construction industry, integrated management of solid waste and regenerative urban and social processes. A presentation of the Lacis evolutionary process requires the demonstration of theoretical principles that underlie its evolution, the origins and stages of its development and the results of the applied research projects.